2018
DOI: 10.3892/etm.2018.5792
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of prostate cancer DU145 cell growth with small interfering RNA targeting the SATB1 gene

Abstract: Abstract. Prostate cancer is a common visceral cancer of men worldwide. It is important to develop a more effective treatment for prostate cancer to overcome the treatment resistance that occurs with recurrence. RNA interference has been demonstrated to be a powerful tool for gene knockdown and has potential as a cancer treatment. It has been previously demonstrated that staining of special AT-rich sequence-binding protein 1 (SATB1) was stronger in prostatic carcinoma with metastasis compared with prostatic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…We found that antibody-free nanocarrier and antibody-functionalized nanocarrier triggered very week response of a small number of genes in vitro. Most of the genes deregulated by NaA-silane-PEG and NaA-silane-PEG-D2B encode proteins involved in both stimulation and suppression of pro-inflammatory responses [35][36][37][38][39]. Simultaneous deregulation of genes encoding proteins that are key to both pro-inflammatory and antiinflammatory responses in the same cell line does not allow a definitive statement about the immunotoxicity of these carriers.…”
Section: Discussionmentioning
confidence: 99%
“…We found that antibody-free nanocarrier and antibody-functionalized nanocarrier triggered very week response of a small number of genes in vitro. Most of the genes deregulated by NaA-silane-PEG and NaA-silane-PEG-D2B encode proteins involved in both stimulation and suppression of pro-inflammatory responses [35][36][37][38][39]. Simultaneous deregulation of genes encoding proteins that are key to both pro-inflammatory and antiinflammatory responses in the same cell line does not allow a definitive statement about the immunotoxicity of these carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, targeting SATB1 is of importance in PCa therapy. It was shown that downregulation of SATB1 using siRNA can pave the way for a reduction in growth, proliferation, and metastasis of PCa cells [ 77 ]. The siRNA-mediated Bcl-xL downregulation potentiates the inhibitory effect on the malignancy and growth of PCa cells [ 78 ].…”
Section: Sirna Targets Signaling Pathways: Focus On Pca Therapymentioning
confidence: 99%
“…Based on literature data, toxicogenomics serves as a promising tool to explore nanocarrier-associated immunotoxicity and related processes such as hypersensitivity, immunogenicity, autoimmunity, and immunosuppression [ 56 , 106 , 107 ]. In contrast to the above-mentioned information, Lankoff et al [ 56 ] could not draw a conclusion regarding the in vitro immunotoxic effects of NaA nanozeolite nanocarriers (NaA-silane-PEG and NaA-silane-PEG-D2B) because they experienced the deregulation of both the pro- and anti-inflammatory genes induced by these nanocarriers [ 56 , 108 , 109 ]. For this reason, relevant studies are required to uncover those aspects of nanoparticle-related toxicity that are poorly understood yet.…”
Section: Introductionmentioning
confidence: 99%